Microbiological and antimicrobial pattern of diabetic foot ulcers (DFUs) at a tertiary care center in North West, Pakistan - Muhammad Arshad Siddiqui; Hamza Naeem; Muhammad Mohsin Ali; Fawad Ahmad Randhawa; Shahida Nazir; Fizza Farooqui (Journal of the Pakistan Medical Association, 2021)
Objective: To determine the pattern of antimicrobial sensitivity of common microorganisms isolated from diabetic foot infections presenting at a tertiary care center in North West, Pakistan. Methods: 201 patients were included in the study, which was conducted over a period of 08 months from January 2019 to August 2019, at the Diabetes & Footcare Clinic (DFC), Mayo Hospital Lahore. Deep-seated tissue samples (0.5 x 0.5 cm) were taken from ulcer bed and immediately sent for culture & sensitivity (C&S) testing. Antimicrobial susceptibility was determined in accordance with Clinical & Laboratory Standards Institute (CLSI) guidelines. Statistical analysis was performed using SPSS version 26.0. Data was presented as Mean ± SD for continuous variables & frequency with percentage for categorical variables. Results: Mean age of participants was 53.05 ± 10.70, from which 66.7 % (134) were male. Grade 3 DFUs (51.7%) and grade 2 DFIs were most prevalent (62.7%). Out of 201 tissue specimens, 389 bacterial isolates were collected. Monomicrobial specimens accounted for 28.4%, with the rest (71.6%) being polymicrobial. Gram negative organisms were 238 (61.11%) while the rest (38.89%) were gram positive organisms. There was a high incidence of methicillin resistant S. aureus (MRSA) at 64.58%. Highest susceptibility of S. aureus was reported with vancomycin and fusidic acid at 100% and 79.35%. Continuous...